Effect of husband education in childbirth support on women's self-efficacy and labor outcomes: a quasi-experimental study - Apri Sulistianingsih; Fitria Fitria; Yeti Septiasari; Desi Madiyanti; Sumi Anggraeni; Indah Sasih (Kashan University of Medical Sciences, 2023)
Background: Labor is an experience that requires confidence but can induce a feeling of fear. Women's readiness and self-efficacy for pregnancy and childbirth are issues in preventing long labor. The husband's support can increase the mother's childbirth self-efficacy.Objectives: To determine the effect of husband education in childbirth support on women's childbirth self-efficacy and labor outcomes.Methods: A quasi-experimental study with pretest-posttest design was conducted from June to October 2022 at the Independent Midwifery Practice Centers of Pringsewu Regency, Indonesia. The participants were 138 pregnant women who were randomly allocated into two groups. The data collection instrument included the Childbirth Self-Efficacy Inventory (CBSEI), a questionnaire for assessing the husbands' childbirth support knowledge and skills, and two questionnaires developed by the researchers to record respondents' characteristics and current pregnancy outcomes. Data analysis was performed using the chi-square test, the independent samples t-test, and the Multivariate analysis of variance.Results: There was a significant increase in the husband's knowledge and skills in childbirth support, four domains of childbirth self-efficacy, pain, duration of the first and second stages of labor, and success of initiating breastfeeding (P <0.001). Multivariate analysis showed that of all variables, the variable most influenced by the intervention was first-stage self-efficacy expectancy, which was 0.746 (74.6%), while the variable least influenced was the duration of the first stage of labor, which was 0.199 (19.9%).Conclusion: Husband education in childbirth support can increase the mother's childbirth self-efficacy and birth outcomes.